Physical Considerations for Understanding Responses of Biological Systems to Low Doses of Ionizing Radiation: Nucleosome Clutches Constitute a Heterogeneous Distribution of Target Volumes. Issue 3 (March 2016) - Howell, Roger W.
Abstract : Abstract: Humans are exposed to low doses of ionizing radiation that arise from a variety of sources. The response of biological systems to low doses of ionizing radiation depend on many factors. Some of the physical factors include distribution of the radiation sources, radiation track structure, structure and dimensions of the biological targets, temporal patterns of radiation exposure(s), absorbed dose rate and total absorbed dose. Recent discoveries suggest that assumptions regarding the structure of an important biological target, namely chromatin, may not be correct. It is now believed that chromatin fiber consists of heterogeneous groups of nucleosomes called clutches, and the distribution of clutch sizes differs between somatic cells and stem cells. This shift in paradigm may have implications for radiation target theory and its explanation of observations of clustered DNA damage.